Tata Kelola Digital dalam Pencegahan Kecurangan pada Program Makan Bergizi Gratis: Peran Pengendalian Internal dan Audit Internal Pemerintah - Yohanes Sugiyanta; Rakhmat (Research and Development Agency Ministry of Home Affairs, 2026)
The Free Nutritious Meal (Makan Bergizi Gratis) program is a strategic national policy for strengthening human capital in Indonesia; however, its implementation is subject to significant fiscal and governance risks arising from the complexity of decentralized supply chains. This study aims to develop an integrated fraud prevention model, termed Smart-Nutri Governance, by combining digital governance architecture with continuous auditing mechanisms. This study employs a design-based policy research approach, using regulatory gap analysis and comparative policy analysis against India's Mid-Day Meal Scheme (Pradhan Mantri Poshan Shakti Nirman) and Brazil's National School Feeding Program (Programa Nacional de Alimentação Escolar). The analysis identifies three critical governance gaps: data validity (ghost recipients), price volatility, and audit detection lag. A simulation using West Java Province data estimates potential fiscal losses of up to 1.15 trillion Indonesian rupiah per year due to inefficiencies in beneficiary validation. To address these gaps, this study proposes a three-layer digital control architecture: (1) real-time biometric or QR-based validation at the point of service, (2) mandatory e-marketplace procurement to ensure price transparency and audit trails, and (3) artificial intelligence–based continuous auditing for real-time anomaly detection. The findings indicate that this model is projected to enhance control effectiveness and offer greater supervisory value compared to conventional post-audit approaches. This study contributes theoretically by integrating Fraud Diamond Theory with digital governance and continuous auditing in the public sector context. Practically, it provides an applicable and adaptive policy framework for strengthening financial accountability in large-scale social assistance programs.